Smart kitchen mobile based application with Arduino module features - Ahmad Luqman, Nazrudin; Anis Farihan, Mat Raffei; Nur Shamsiah, Abdul Rahman (2021)
Kitchen is one of the important areas in the house as the kitchen serves many functions especially the cooking activity. Moreover, kitchen management such as managing the groceries items, electricity usage as well as gas management are also crucial activities in kitchen. Hence, a smart kitchen mobile based application with Arduino module features is developed which have four main functions: (i) to produce a recipe recommendation from available ingredients using fuzzy logic, (ii) to have a grocery tracker function, (iii) expiry notification function, and (iv) arduino features that enable user to control kitchen lamp, motion sensor and gas detection alarm.